Development of Site-Specific PEGylated Granulocyte Colony Stimulating Factor With Prolonged Biological Activity - Kumari, Monika; Sahni, Girish; Datta, Sonal (Frontiers in Bioengineering and Biotechnology, 2020)
Currently, amino-terminal PEGylated human granulocyte colony stimulating factor (huG-CSF) is used to prevent and treat neutropenia. Although huG-CSF has been used as a drug for more than 20 years, it has three significant drawbacks: (i) it relies on PEG aldehyde for PEGylation of the alpha-amino group of the first amino acid, and this leads to non-specific PEGylation of epsilon amino group of lysine residues within the G-CSF (ii) longer-acting G-CSF variants are desirable to reduce the risk of chemotherapy-associated neutropenia (iii) G-CSF cannot be administered on the day of chemotherapy. In an attempt to overcome the above drawbacks, we engineered cysteine variants of G-CSF to facilitate the maleimide PEG-based site-specific PEGylation that leads to highly homogenous PEGylated product. Importantly, we have demonstrated that 20 kDa thiol-reactive PEG conjugated by maleimide chemistry to the Cys2 G-CSF variant exhibits leukocyte proliferative activity similar to that of the commercially available G-CSF conjugated with aldehyde PEG in neutropenic mice model. Moreover, we have demonstrated that PEGylation of cysteine variant of huG-CSF with higher molecular weight PEGs, such as 30 kDa PEG and 40 kDa PEG lead to significantly prolonged leukocyte proliferation activity compared to the variant conjugated with 20 kDa PEG. Importantly, even half-dose of the engineered variant conjugated with 40 kDa PEG exhibited significantly longer biological activity than the commercially available 20 kDa PEGylated huG-CSF. Finally, we have demonstrated that administration of engineered variant conjugated with 40 kDa PEG on the day of administration of cyclophosphamide for inducing neutropenia in mice can alleviate neutropenia through leukocyte proliferation. In summary, this study provides the design of site-specific PEGylated huG-CSF variants with improved therapeutic potential. It opens the possibility of long-acting and same-day prophylactic administration of G-CSF after chemotherapy drug regimens. These results may pave the way for the development of potential G-CSF derivatives possessing longer half-lives and favorable clinical attributes.